Exploring the opinions of secondary school students on the strengths and weaknesses of the school dental service in Selangor, Malaysia: A qualitative study - Nazirah Ab Mumin; Zamros Yuzadi Mohd Yusof; Jamaludin Marhazlinda; Unaizah Obaidellah (BMC Series (Springer Nature), 2024)
Indexed by WOS/Scopus/ERA